Does it still fit? - Adapting affordance judgments to altered body properties in young and older adults. - Lisa Finkel; Katharina Schmidt; Jean Patrick Philippe Scheib; Jennifer Randerath (PLoS ONE)
Actor-related affordance judgments are decisions about potential actions that arise from environmental as well as bodily and cognitive conditions. The system can be challenged by sudden changes to otherwise rather stable actor references e.g. due to accidental bodily injuries or due to brain damage and resulting motor and cognitive constraints. The current study investigated adaptation to suddenly artificially altered body properties and its reversibility in healthy young versus older adults. Participants were asked to judge whether they would be able to fit their hand through a given horizontal opening (Aperture Task). Body alterations were induced by equipping participants with one hand splint for 24 hours that enlarged the hand in width and height. Participants were tested before and directly after putting the splint on as well as after a habituation period of 24 hours. To assess reversibility, participants were tested again directly after removing the splint and one day later. Judgment accuracy values and detection theory measures were reported. Both, young and older adults judged more conservatively when body properties were altered compared to initial judgments for normal body properties. Especially older adults showed major difficulties in such quick adaptation. Older adults' judgment accuracy as well as perceptual sensitivity were significantly lowered when body properties were suddenly altered. Importantly, lowered judgment performance occurred for both, the splinted as well as the non-splinted hand in older adults. Only after 24 hours of habituation, older adults tended to regain initial performance levels showing adaptive behavior to the altered condition. Removing the hand splint for one day was sufficient to reverse these adaptive effects. Our study results suggest that aging slows down adaptation to sudden bodily alterations affecting actor-related affordance judgments. We propose that these altered processes may go along with uncertainty and a heightened concern about potential consequences of misjudgments. Clearly, future studies are needed to further elucidate the underlying processes of adaptation in affordance judgments. These may reveal major implications for the aging society and its associated problems with an increased risk of falling or stroke related bodily constraints.